The Influence of Motion Graphics on User Experience in Interactive Media - Wahyu Pamekas, Bondan; Irawan, Nico (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The influence of Motion graphics on the user experience within interactive media, nevertheless, is less clear. User engagement, information retention and satisfaction in interactive media. An evaluation of the impact of motion graphics The study was conducted with an experimental technique having two category users one is containing motion graphics and second without them, we collect data from questionnaire n behavioural analysis. The results of this research showed that the average time span for interaction (interaction time) using motion graphics in Interactive Media was 18.86 minutes better than those who did not use it where they get a value of 12.71 minutes The motion graphics group retained information at a rate of 86.43%, compared to the other cluster without any frames, which was just 65.14%. The user satisfaction was also better, with an average score of 8.71 in the group with motion graphics than it is for 6.57 without animation. Motion Graphics is a key factor which together increases user engagement, information retention and satisfaction.